2004
DOI: 10.1152/ajpheart.00965.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cell transplantation for treatment of acute myocardial infarction: unique capacity for repair by skeletal muscle satellite cells

Abstract: An adult heart injured by an ischemic episode has a limited capacity to regenerate. We administered three types of adult guinea pig cells [cardiomyocytes (CMs), cardiac fibroblasts (CFs), and skeletal myoblasts (Mbs)] to compare their suitability for repair of acute myocardial infarction. We used confocal fluorescent microscopy and a variety of specific immunomarkers and echocardiography to provide anatomic evidence for the viability of such cells and their possible functional beneficial effects. All cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…Skeletal myoblasts (SkMs) appear more attractive compared to other cell types because of their resistance to ischemia, high proliferative potential, autologous source and their ability to generate a contractile phenotype [Menasché, 2004]. Most studies have shown an improvement in heart function with SkM transplantation [Horackova et al, 2004;Gavira et al, 2006]. However, SkM transplantation is con-fronted with some problems.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal myoblasts (SkMs) appear more attractive compared to other cell types because of their resistance to ischemia, high proliferative potential, autologous source and their ability to generate a contractile phenotype [Menasché, 2004]. Most studies have shown an improvement in heart function with SkM transplantation [Horackova et al, 2004;Gavira et al, 2006]. However, SkM transplantation is con-fronted with some problems.…”
Section: Introductionmentioning
confidence: 99%
“…Adult-derived stem cells may hold promise for the treatment of heart failure since they can be used for autologous transplantation (5). Several types of adult stem cells such as bone marrow stem cells (BMSCs), skeletal myoblasts, and cardiac stem cells have been studied extensively for their capacity of cardiac repair (7,18,20,21,34). A number of animal studies have demonstrated therapeutic benefits of the adult stem cells for myocardial infarction (5,7,18,20,21,34).…”
mentioning
confidence: 99%
“…Transplantation of SMs into models of MI showed that they have the ability to replace cardiomyocyte loss and restore a degree of cardiac function (Taylor et al, 1998;Reinecke and Murry, 2000;Horackova et al, 2004). To improve the efficacy of SM transplantation, many teams have focused on overexpressing growth factors such as VEGF (Ye et al, 2007;Aharinejad et al, 2008;Rong et al, 2008).…”
Section: Cd45mentioning
confidence: 99%